Utilization of multipurpose tree prunings as a source of nitrogen for the production of rape (Brassica napus L.) and spinach (Spinacea olearacea L.) - Madakadze, I.C. (Ignacio Casper) (University of Pretoria, 2014)
Dissertation (MSc Agric)--University of Pretoria, 2013.